Vad upplever chefer är viktigt för att kunna utföra ett framgångsrikt ledarskap i ledning av grupper? - Klingvall,Amanda; Smogorzewski,Emma; Öjevall,Molly (2026)
This study aims to illustrate what managers consider important for a successful leadership, with the goal to highlight new perspectives on leadership for managers so they can develop and have a greater understanding of how other managers think about leadership. It also provides practical examples of how other managers lead that can inspire more managers to lead successfully. Through a qualitative approach ten participating managers were interviewed semistructurally and asked to describe what they thought contributed to a successful leadership. The results were analysed and compiled to six major themes: 1) coworkers contribution and cooperation, 2) openness, trust and safety, 3) communication, 4) leadership and personal attributes, 5) presence, 6) organizational resources and time. Based on the themes, the participants mainly talked about situational leadership, followed by communication, clarity and the right organizational conditions. Personal qualities such as being present, open and having the ability to create trust were also contributing factors, as well as relevant knowledge and experience. The themes were later discussed and connected to several psychological theories and past research in order to contribute different perspectives on successful leadership.
Keywords: Ledarskap; framgångsrikt ledarskap; chefskap; situationsanpassat ledarskap; tematisk analys; leadership; successful leadership; management; situational leadership; thematic analysis